Pengaruh Motivasi, Pengalaman Organisasi, dan Lingkungan Kerja Terhadap Komitmen Organisasi pada Volunteer Better Youth Foundation Surabaya - Ainurriyah; Santoso, Bowo (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The study aims to: (1) To analyze the effect of motivation on organizational commitment in Better Youth Foundation Surabaya volunteers. (2) To analyze the effect of organizational experience on organizational commitment in Better Youth Foundation Surabaya volunteers. (3) To analyze the effect of work environment on organizational commitment in Better Youth Foundation Surabaya volunteers. The method used is quantitative method with SMARTPLS analysis tool. The population in this study was the same as the sample of 56 volunteers. The findings in this study indicate that organizational experience and work environment contribute to organizational commitment, while motivation does not contribute to organizational commitment.